Inculcating Halal Values in Seaweed Production for Competitive Positioning - Mohammad Noor, Normawaty; Muhammad Noor, Sarina; Weliyadi, Encik; Salleh, Rukisah (IIUM Medical Journal Malaysia, 2018)
Seaweed industry is important in several countries including Malaysia, Japan, Indonesia, and the Philippines. The seaweed, Kappaphycus is widely used in a variety of food products as an excellent nutritional supplement. There are several stages in producing raw Kappaphycus for industry such as cultivation and harvest. Most of these steps follow a traditional way which has been practiced from one generation to another. As seaweed is part of the main ingredients in many final produce, its processing must incorporate cleanliness and quality aspect. Therefore, a focus on Halal is of utmost importance. Halal is a concept that stresses on shariah law and ensuring the utmost quality which benefits most producers especially in food and supplement products. However, the knowledge of Halal is still limited in marine production including seaweed. The seaweed process has gone through numerous stages yet none of them has been checked on its Halalness aspect. This study is to deliberate on the aspect of Halalness for each stage involved, including cultivation and harvesting. To achieve this, observations and literature search were performed and findings showed that there is lack of hygienic practices in handling seaweed production. Therefore, conjoint initiatives among university-industry-government are needed to enhance the value proposition of the seaweed production as it complies with the concept of Halalness. This will contribute towards the development of Halal ecosystem from seed to harvest of quality seaweed production.